Global food efficiency of climate change mitigation in agriculture - Kleinwechter, U.; Levesque, Antoine; Havlík, Petr; Forsell N; Zhang Y; Fricko O; Obersteiner, Michael (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2015)
Concerns exist regarding potential trade-offs between climate change mitigation in agriculture and food security. Against this background, the Global Biosphere Management Model (GLOBIOM) is applied to a range of scenarios of mitigation of emissions from agriculture to assess the implications of climate mitigation for agricultural production, prices and food availability. The "food efficiency of mitigation" (FEM) is introduced as a tool to make statements about how to attain desired levels of agricultural mitigation in the most efficient manner in terms of food security. It is applied to a range of policy scenarios which contrast a climate policy regime with full global collaboration to scenarios of fragmented climate policies that grant exemptions to selected developing country groups. Results indicate increasing marginal costs of abatement in terms of food calories and suggest that agricultural mitigation is most food efficient in a policy regime with global collaboration. Exemptions from this regime cause food efficiency losses.